Terrien’s marginal degeneration: an unusual presentation in an Indian female - Jain, K; Kumar, S; Jain, C; Malik, VK (Nepalese Journal of Ophthalmology, 2010)
An interesting case of bilateral corneal ectasia resulting from its marginal degeneration in a young female is reported. Terriens marginal degeneration is a rare disorder of unknown etiology. It is usually bilateral, although often asymmetric, and is seen mainly in young men. It generally starts superiorly as marginal opacification and stromal thinning. This case was unique in that, unlike routine presentation seen in this type of disorder, the gutter was located more anteriorly in the cornea and was not associated with any vascularization. Keyword: ectasia; keratoconus; Terrien's marginal degeneration DOI: 10.3126/nepjoph.v1i2.3691 Nep J Oph 2009;1(2):141-142